2020
DOI: 10.1002/ldr.3741
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the degradation of grassland ecosystems based on the advanced local net production scaling method—The case of Inner Mongolia, China

Abstract: The gradual degradation of grasslands on a global scale goes hand‐in‐hand with significant challenges for agriculture and animal husbandry development. Numerous relevant policies and projects have been implemented to protect and restore Chinese ecosystems, but it is still unclear to what degree grassland ecosystems can be recovered. In view of this, we constructed an advanced local net production scaling (ALNS) method by replacing the classification method by self‐organizing feature maps (SOFM) and tailoring t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 75 publications
(94 reference statements)
0
6
0
Order By: Relevance
“…The LNS method requires that most pixels within an LCC have a uniform productive potential so that DS is determined relative to it. Therefore, the magnitude of desertification is depicted by the gap between actual and potential productivity (Lang et al, 2020;Prince et al, 2009), and the DS is expressed as:…”
Section: Local Net Primary Production Scalingmentioning
confidence: 99%
See 2 more Smart Citations
“…The LNS method requires that most pixels within an LCC have a uniform productive potential so that DS is determined relative to it. Therefore, the magnitude of desertification is depicted by the gap between actual and potential productivity (Lang et al, 2020;Prince et al, 2009), and the DS is expressed as:…”
Section: Local Net Primary Production Scalingmentioning
confidence: 99%
“…Although the percentile-based one can overcome the bias of anomalies, the choice of percentile is a subjective preference (Lang et al, 2020;Wessels et al, 2008). Therefore, establishing a robust framework to determine the NPP p is especially important for the widespread application of LNS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on grassland degradation assessment are mainly based on remote sensing technology and parameter assessment systems ( Gao et al, 2006 ; Feng et al, 2009 ; Lang et al, 2021 ). When using this method, indexes for grassland degradation are always uncertain, and most index parameters are set according to the subjective experience of researchers, resulting in the results being unreliable.…”
Section: Introductionmentioning
confidence: 99%
“…The areas have been used inappropriately, through an excessive load of animals, which has caused environmental impacts due to vegetation cover loss, invasion of exotic species, and soil erosion [8,9]. Studies have shown that pasture ecosystem degradation not only alters its structure and ecosystem productivity but also affects surface-atmosphere interactions, changing heat and water transport [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%